STRATEGI KOMUNIKASI PEMASARAN JAM TANGAN MATOA DALAM MENINGKATKAN BRAND AWARENESS - Susanto Susanto; Afrina Sari (Universitas Teuku Umar, 2020)
This research is about marketing communication strategies by Matoa Watches in increasing brand awareness. Marketing communication conducted by Matoa is more focused on marketing communication activities on social media and internet but also done through advertising (advertising), exhibitions, publications, sales promotion and direct marketing to rise a brand awarenes.. In this research, researchers used a descriptive qualitative method with data collection techniques using in-depth semi-structured interviews to obtain complete information in accordance with what is needed by researchers. The conclusion from this study shows that every promotion mix undertaken by Matoa not only refers to increasing brand awareness to the community but there are several promotional mixes aimed at increasing sales such as sales promotion and direct marketing.Keywords: Marketing Communication Strategies, Intergrated Marketing Communication (IMC), Brand Awareness¸ Promotion